Study on ultra-precision compliant mechanisms for nanotechnology applications - Du, Hejun (2008)
Including: 2 parts. Compliant mechanisms provide motion through elastic deformation under the action of external loads. These mechanisms are key functional members in many today's precision machines and devices, such as precision micro-positioning stages, micro actuators, microelectromechanical systems (MEMS) and robots, where micron or even nanometric resolution and accuracy are required for the motion. On the contrary to rigid-body mechanisms, compliant mechanisms consist of monolithic construction without rigid joints or sliders. Thus, they effectively eliminate the wear, backlash, lubrication, and friction problems, which are often encountered by rigid-body mechanisms.